2010
DOI: 10.1073/pnas.0908315107
|View full text |Cite
|
Sign up to set email alerts
|

The dimensionality of discourse

Abstract: The paragraph spaces of five text corpora, of different genres and intended audiences, in four different languages, all show the same two-scale structure, with the dimension at short distances being lower than at long distances. In all five cases the short-distance dimension is approximately eight. Control simulations with randomly permuted word instances do not exhibit a low dimensional structure. The observed topology places important constraints on the way in which authors construct prose, which may be univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…The structure and dynamics of human experience described in this series of studies (Doxas et al., ; Sreekumar et al., ; this study) validate the assumptions of some theories of memory and call into question the assumptions of others. An influential verbal model (Conway & Pleydell‐Pearce, ) proposed that autobiographical memories arise from an interaction between components of an underlying knowledge base and a current set of goals maintained in the working self mediated by control processes.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…The structure and dynamics of human experience described in this series of studies (Doxas et al., ; Sreekumar et al., ; this study) validate the assumptions of some theories of memory and call into question the assumptions of others. An influential verbal model (Conway & Pleydell‐Pearce, ) proposed that autobiographical memories arise from an interaction between components of an underlying knowledge base and a current set of goals maintained in the working self mediated by control processes.…”
Section: Discussionsupporting
confidence: 66%
“…We used methods selected from the dynamical systems toolbox to analyze an email corpus of 30,823 emails and showed that the structure of personal discourse as described by the correlation dimension is two‐scaled as are the structures of reading experience (fig. 2 in Doxas et al., ) and visual experience (Fig. and fig.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations